Assessment of COPD-Related Knowledge Among Internal Medicine Nurses: A Cross-Sectional Study - Ma, Yiming (Int J Chron Obstruct Pulmon Dis, 2019)
BACKGROUND: Since most internal medicine nurses work with chronic obstructive pulmonary disease (COPD) patients daily, their ability to meet the needs of COPD patients is an important issue. Our study aimed to assess COPD-related knowledge in internal medicine nurses. METHODS: A descriptive cross-sectional study including 175 participants was conducted to investigate COPD-related knowledge levels among internal medicine nurses in a large top-ranked tertiary hospital in China. The Bristol COPD Knowledge Questionnaire (BCKQ) was used to test COPD-related knowledge levels in the participants. RESULTS: Overall BCKQ score for all nurses in this study was 35.76 ± 5.49. In comparison with non-respiratory nurses, the overall score among respiratory nurses was significantly higher (39.01 ± 3.95 vs 33.32 ± 5.23, p < 0.001). The mean scores for four topics (epidemiology, breathlessness, oral steroids, and inhaled steroids) were less than 3 among both respiratory and non-respiratory nurses. Subgroup analysis of specialist respiratory wards showed that nurses in the chronic airway disease ward had the highest overall knowledge score (40.47 ± 4.03). Linear regression analysis demonstrated that the overall BCKQ score was significantly related to the population of nurses (β coefficient = 3.016, 95% confidence interval [CI]: 0.953–5.079, p < 0.01), education (β coefficient = 4.710, 95% CI: 1.979-7.440, p < 0.01) and previous rotation in respiratory wards (β coefficient = 3.871, 95% CI: 1.776-5.967, p < 0.001). CONCLUSION: Internal medicine nurses at this tertiary hospital showed deficits in COPD-related knowledge. Appropriate and systematic education about COPD knowledge and strengthening rotation among different wards are necessary for improving COPD-related knowledge levels among internal medicine nurses.